Competitive strategies for water availability in two Mediterranean Quercus species - Nardini, A.; Gullo, M. A. Lo; Salleo, S. (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.
Keywords: leaf conductance; leaf water status; Quercus cerris (Turkey Oak); Quercus suber (cork oak); root hydraulic conductance.

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd